Intra-observer reliability of the anthropometric measurements in South American children and adolescents : the SAYCARE Study (2019)
ABSTRACT: The South American Youth/Child Cardiovascular and Environmental (SAYCARE) feasibility study aims to develop valid and reliable indicators to investigate health-related behavior and nutritional status in children and adolescents. Anthropometric measurements are one of the evaluated indicators in the study. The accuracy of the anthropometric data is very important and relies in the quality of the measurements. Objective: to describe the intra-observer reliability of ten anthropometric measurements: weight, height, circumferences (neck, arm, waist, hip) and skinfolds (triceps, subscapular, biceps and suprailiac) of children and adolescents from six South American cities: Lima, Medellin, Montevideo, Santiago, San Pablo and Teresina. Methods: prior to the study, fieldworkers from the seven centers participated in central training to ensure the application of standardized pro- cedures in the anthropometric measurements. Intra-observer precision, technical error of measurement (TEM) and coefficient of reliability (R) were estimated for each measurement. Results: reliability of weight and height was above 99% in almost all cities. TEM for skinfold thickness was below 1.4 mm in children and 2.13 mm in adolescents, while reliability was above 95% in most of the skinfold measurements. TEM for circumferences was below 1.8 cm in children and 0.64 cm in adolescents, while reliability was above 99% in almost all circumferences. Conclusions: reliability of the anthropometric measurements in this study was high. In comparison with similar European or American studies, the reliability of the measurements taken in our study was, in most cases, similar or even higher.